1982
DOI: 10.1246/bcsj.55.3051
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Studies on the Mistletoe. IV. The Structure of Isoglucodistylin, a New Flavonoid Glycoside Isolated from Taxillus kaempferi

Abstract: A new flavonoid glycoside, isoglucodistylin was isolated from Taxillus kaempferi, and (2R,3S)-taxifolin 3-β-d-glucopyranoside was assigned to this substance from studies on the hydrolysis products and on the isomerization products, and from analyses of the carbon-13 NMR spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The ESI-MS/MS of the compounds also showed a major fragment at m/z 305.0, which is diagnostic of a flavanone nucleus of the 2,3-dihydroquercetin structure. (Markham & Mabry 1968;Düber et al 1997), 2R,3S-dihydroquercetin-3-O-b-D-glucopyranoside (isoglucodistylin) (2) (Sakurai et al 1982;Düber et al 1997) and 2R,3R-dihydroquercetin-3-O-a-L-arabinopyranoside (3) (Chosson et al 1998) (Figure 1). This is the first report of the isolation of these compounds from this plant species.…”
Section: Resultsmentioning
confidence: 99%
“…The ESI-MS/MS of the compounds also showed a major fragment at m/z 305.0, which is diagnostic of a flavanone nucleus of the 2,3-dihydroquercetin structure. (Markham & Mabry 1968;Düber et al 1997), 2R,3S-dihydroquercetin-3-O-b-D-glucopyranoside (isoglucodistylin) (2) (Sakurai et al 1982;Düber et al 1997) and 2R,3R-dihydroquercetin-3-O-a-L-arabinopyranoside (3) (Chosson et al 1998) (Figure 1). This is the first report of the isolation of these compounds from this plant species.…”
Section: Resultsmentioning
confidence: 99%
“…This species is a small herb found in extreme southern regions of South America, including Patagonia, Tierra del Fuego, and the Falkland Islands. To the best of our knowledge, there have been no previous phytochemical studies on the genus Nanodea , but other phytochemical studies of various species belonging to the same family have revealed the presence of saponins, alkaloids, coumarins, flavonoid glycosides, lignans, iridoids, sesquiterpenes, and fatty acids …”
mentioning
confidence: 99%
“…The isomerization of flavanonols at C-2, C-3 is not without precedent, as it was described for taxillusin – the flavanonol glycoside from Taxillus kaempferi (Japanese mistletoe) containing the 3-hydroxy-2,3-dihydro-2-phenylchromen-4-one moiety [ 29 ]. Taxillusin ( 24 , (2 R ,3 R )-taxifolin 3-β-D-glucopyranoside 6''-gallate, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism for the isomerization of silybin at C-2, C-3 was inspired by these previous studies, i.e., involving an enolization stage (route II in Scheme 5 ) [ 29 34 ]. In EtOAc, the isomerization can occur from 1a or from its acetylated counterpart ( 2a ), since the 23- O -acetylation proceeds in parallel with the isomerization and is substantially faster than the isomerization reaction.…”
Section: Resultsmentioning
confidence: 99%